A uses and gratifications approach to considering the music formats that people use most often. (May 2021) - Krause, Amanda E; Brown, Steven Caldwell
With many ways for consumers to access and consume music, little is known about why people choose to listen to music via one format over another. Using a uses and gratifications approach, the present research used an online questionnaire ( N  = 396) to examine people's format use, concerning six particular formats. The results suggest that eight dimensions, namely, usability and intention to use, discovery, functional utility, flexibility, connection, social norms, value for money, and playback diversity, define the uses and gratifications that particular formats serve. When considering whether format use was related to broader music engagement behaviors, results indicated different associations between music engagement variables and format use suggesting that different formats allow listeners to engage with music in unique ways. Findings have implications for future research that examines how and why people engage with music listening in everyday life, elaborating further our understanding of how selection of particular formats can lead to different listening experiences.